Evolusi Arsitektur Komputasi dan Protokol Internet Awal: Analisis Historis Teknis Generasi Pertama - Muhammad Arif Sirait; Ijlal Rafif Sitorus; Muhammad Rafly Mumtaz; Syamil Bashrah; Tondi Al Habib Tanjung; Said Hambali Takhir (Samudra Ilmu Indonesia, 2026)
This study aims to analyze the evolutionary history of first-generation computer architecture and internet protocols, as well as their impact on technological developments in Indonesia. Data processing in the pre-digital era, which relied heavily on mechanical devices and manual calculations, spurred the birth of electronic computing innovations such as ENIAC and EDVAC. Using a descriptive qualitative method based on a Systematic Literature Review (SLR), this article explores the critical transition from isolated computing to global system networks. The main findings indicate that the adoption of Von Neumann Architecture and the shift from circuit switching to packet switching via TCP/IP protocols revolutionized processing efficiency and universal data transmission. In Indonesia, early infrastructure limitations actually triggered socio-technical creativity, such as the development of RT/RW Net and the use of open-source technology pioneered by figures like Onno W. Purbo. This research concludes that the principles of decentralization and efficiency from the early era remain relevant in facing future technological challenges such as 5G and Quantum Computing